Effect of nitrogen flushing and storage temperature on flavor and shelf-life of whole milk powder - Lloyd, M.A.; Hess, S.J.; Drake, M.A. (Journal of dairy science, 2009)
The US industry standard for shelf-life of whole milk powder (WMP) is 6 to 9 mo, although previous research has demonstrated flavor changes by 3 mo at ambient storage. This study evaluated the influence of packaging atmosphere, storage temperature, and storage time on WMP shelf-life using sensory and instrumental techniques. Two commercial batches of WMP were repackaged in plastic laminate pouches with air or nitrogen and stored at 2°C or 23°C for 1 yr. Descriptive analysis was conducted using a 10-member trained panel; volatile analysis was performed using solid-phase microextraction with gas chromatography-mass spectrometry. Consumer acceptance (n=75) was conducted every 3 mo with reconstituted WMP and white and milk chocolate made from each treatment. Data were analyzed using ANOVA with Fisher's LSD, Pearson correlation analysis, and principal component analysis. Air-stored WMP had higher peroxide values, lipid oxidation volatiles, and grassy and painty flavors than nitrogen-flushed WMP. Storage temperature did not affect levels of straight chain lipid oxidation volatiles; 23°C storage resulted in higher cooked and milkfat flavors and lower levels of grassy flavor compared with 2°C storage. Consumer acceptance was negatively correlated with lipid oxidation volatiles and painty flavor. Nitrogen flushing prevented the development of painty flavor in WMP stored up to 1 yr at either temperature, resulting in chocolate with high consumer acceptance. Nitrogen flushing can be applied to extend the shelf life of WMP for use in chocolate; storage temperature also plays a role, but to a lesser extent.